2010
DOI: 10.1111/j.1538-7836.2009.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C‐III predicts cardiovascular mortality in severe coronary artery disease and is associated with an enhanced plasma thrombin generation

Abstract: predicts cardiovascular mortality in severe coronary artery disease and is associated with an enhanced plasma thrombin generation. J Thromb Haemost 2010; 8: 463-71.Summary. Background: Apolipopoprotein C-III (apo C-III) plays a pivotal role in controlling plasma triglyceride (TG) and contributes to the atherogenic properties of TG-rich lipoproteins. Objectives: (i) To examine the predictive value of serum apo C-III for cardiovascular mortality in the setting of secondary prevention of coronary artery disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 41 publications
9
63
1
5
Order By: Relevance
“…However, the pathophysiological mechanism of these associations requires further investigation. One study reported that apo C-III is related to increased endogenous generation of thrombin and hence interferes in the coagulation cascade [3]. In this study the association with thrombotic events involved the e2 allele thus suggesting that an increase in the endogenous generation of thrombin should be investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the pathophysiological mechanism of these associations requires further investigation. One study reported that apo C-III is related to increased endogenous generation of thrombin and hence interferes in the coagulation cascade [3]. In this study the association with thrombotic events involved the e2 allele thus suggesting that an increase in the endogenous generation of thrombin should be investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Such concentrations were associated to an enhanced endogenous thrombin generation in plasma suggesting a complex interplay between triglycerides-rich particles and the coagulation cascade as well as a new 'thrombogenic' role for apo C-III [3].…”
Section: Introductionmentioning
confidence: 97%
“…Антисенс-технологии открыли широкую перспективу для попытки воздействия на концентрацию ТГ с исполь-зованием в качестве мишеней генов многочисленных белков, вовлеченных в их метаболизм [7]. Одной из наиболее очевидных мишеней является апоСIII, из-за связи данного апобелка с развитием триглице-ридемии, атеросклероза, ССЗ и других метаболиче-ских нарушений [28,29]. Генетические исследования свидетельствуют о положительном влиянии пони-женного уровня апоСIII на уровень ТГ и атерогенных апоВ100-содержащих липопротеидов, а также на про-должительность жизни [30].…”
Section: препараты на основе антисмысловых олигонуклеотидов (асо)unclassified
“…Differences between the populations, for instance, in the degree of hyperlipidemia, were suggested to be involved in some of these risk associations. Indeed, Olivieri et al found that Apo C‐III was an independent risk factor for CAD and that it was associated with endogenous thrombin potential (ETP) and peak thrombin activity 45. This was not the case for total cholesterol, low‐density lipoprotein, triglycerides, and apoE, suggesting that Apo C‐III may play a functional role in thrombin generation.…”
Section: Literature Studiesmentioning
confidence: 99%
“…From the present analysis, Apo‐CIII and Lp(a) emerge as determinants of TG. Olivieri et al provide an explanation for the effect of Apo‐CIII showing that elevated concentrations of Apo CIII are associated with an increase in thrombin activity to an extent comparable to the carriership of G20210A gene variant and modulating TG in subjects with or without CAD 45. Direct effects of Lp(a) on TG have not been reported.…”
Section: Biochemical Mechanisms Linking Thrombin To Atherothrombosismentioning
confidence: 99%